2022
DOI: 10.1590/fst.12221
|View full text |Cite
|
Sign up to set email alerts
|

Application of skimmed milk freeze concentrated in production of ice cream: physical, chemical, structural and rheological properties

Abstract: Freeze concentration process was used to concentrate milk until the third stage of freeze concentration. Thus, two samples of ice creams were manufacture, one with milk and the other with concentrated milk from the first stage of block freeze concentration, and denominated ice cream 1 and ice cream 2, respectively. Both ice creams were characterized according to physicochemical characteristics, overrun, microscopy, melting rate, texture, color, and rheological properties. The use of concentrated milk influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Góral et al [ 33 ] documented that a low overrun in frozen ice creams is most probably due to a low protein content. This statement is very well supported with the current results where the overrun in all sorbet matrices is significantly low compared to milk-containing ice creams [ 34 ]. Furthermore, Senanayake et al [ 35 ] also validate that fruit ice creams are characterized with lower overrun.…”
Section: Resultssupporting
confidence: 90%
“…Góral et al [ 33 ] documented that a low overrun in frozen ice creams is most probably due to a low protein content. This statement is very well supported with the current results where the overrun in all sorbet matrices is significantly low compared to milk-containing ice creams [ 34 ]. Furthermore, Senanayake et al [ 35 ] also validate that fruit ice creams are characterized with lower overrun.…”
Section: Resultssupporting
confidence: 90%
“…This is probably due to the lower sugar content of these two samples. Camelo-Silva et al (2022) produced ice cream using by skimmed milk (ice cream 1) and concentrated milk (ice cream 2) and found that the overrun value of ice cream 2 had a higher than ice cream 1. This difference can be explained with the physicochemical composition of the ice cream 2 due to the protein content of ice cream 2.…”
Section: Overrunmentioning
confidence: 99%
“…More specifically, Camelo‐Silva et al. (2022) freezed concentrated milk until the third stage and used the sample from the first stage for ice cream production (Ice cream 1). This ice cream was contrasted to the ice cream from regular milk (Ice cream 2), and the authors concluded that Ice cream 1 presented good chemical, physical, rheological, and microstructural properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, FC has been revealed to be very efficient in the maintenance of bioactive compounds, volatile compounds, and biological activity (cytotoxic activity and antioxidant) due to the low temperature (below 0°C) used in the process (Gunathilake, 2020). Therefore, the beneficial effects of FC have been newly reported in blueberry juice (Casas‐Forero, Orellana‐Palma, et al., 2021; Casas‐Forero et al., 2020a, 2020b), strawberry juice (Adorno et al., 2017), orange juice (Haas et al., 2022), pineapple juice (Orellana‐Palma, Zúñiga, et al., 2020), waste potato juice (Kowalczewski et al., 2019), apple juice (Ding et al., 2019; Qin et al., 2019), broccoli extract (Azhar et al., 2020), green tea (Meneses et al., 2021), milk (Camelo‐Silva et al., 2022; Machado Canella et al., 2020), and whey (Barros et al., 2022; De Liz et al., 2020). More specifically, Camelo‐Silva et al.…”
Section: Introductionmentioning
confidence: 99%